Microbial diversity of meat products under spoilage and its controlling approaches - Zhu, Yanli; Wang, Wei; Li, Ming; Zhang, Jiamin; Ji, Lili; Zhao, Zhiping; Zhang, Rui; Cai, Demin; Chen, Lin (Frontiers in Nutrition, 2022)
Meat spoilage (MS) is a complex microbial ecological process involving multiple specific microbial interactions and is vulnerable to numerous events. As consumer demand for meat products increases, the quality and safety of meat products gain much attention. MS is detrimental to people's health and leads to the waste of meat products which will cause huge losses during production, storage, transportation, and marketing. This mini-review summarizes the diversity of spoilage microorganisms in livestock, poultry, and aquatic products, and the approaches to inhibit MS. This would facilitate the targeted development of technologies against MS, to extend meat’s shelf life, and effectively diminish food waste and economic losses.